Intervention of Local Resource-Based MSME Human Resource’s Competency Development - Suyatno, Suyatno; Suryani, Dewi Amanatun (Universitas Medan Area, 2024)
This research aims to obtain a comprehensive and complete picture of local potential-based MSME HR competency development interventions in improving the community economy in Girikerto Village. The findings of this research are that the Girikerto community has various local resources that are developed and utilized to become more economically valuable and competitive. Interventions for developing MSME HR competencies have been carried out by relevant stakeholders consisting of government, academics, supporting institutions, and funding institutions in the form of policies, training programs, mentoring, development, and facilitation in a coordinative and collaborative manner. This research focuses on interventions to develop MSME HR competencies, while previous studies have focused more on the importance of competencies, types of competencies, and the role of HR competencies in MSMEs. This research uses qualitative methods, primary data collection was carried out through observation and interviews with the MSME's Actor in Girekerto, while secondary data was obtained from documents, articles, and social media. The findings from this research have implications for the Village Government and related institutions in preparing intervention strategies for developing MSME HR competencies based on local potential. The government must intervene in collaboration and coordination with related institutions in formulating policies, programs, and facilitation for MSME groups based on available resources. Policies, programs, and facilitation must be carried out continuously and coordinatedly.